PENGARUH KECERDASAN SPIRITUAL DAN DISIPLIN TERHADAP KINERJA GURU DI SD AL FIRDAUS SURAKARTA - Ari Wibowo; R Arie Febrianto (ITB AAS INDONESIA Surakarta, 2020)
The objectives of this study were: (1) To measure and test the influence of spiritual intelligence and discipline on teacher performance at SD Al Firdaus Surakarta. (2) To measure and test the interaction of spiritual intelligence and discipline on teacher performance at SD Al Firdaus Surakarta. The number of samples in this study were 28 respondents, with the sampling technique using a census. The results of the regression analysis found that there was a positive and significant effect of spiritual intelligence and discipline on teacher performance at SD Al Firdaus Surakarta. The results of the t test and the F test prove that the variables of spiritual intelligence and discipline have a positive and significant effect both partially and simultaneously on teacher performance. Based on the value of the coefficient of determination which has a positive value of 0.66, it shows that the performance of teachers at SD Al Firdaus Surakarta can be explained by the spiritual intelligence and discipline variables of 66.0%, while the remaining 34.0% is explained by other factors that are not observed in this study. Keywords: spiritual intelligence, discipline, teacher performance and regression